'It was pop that was making the bread': Accounting and musical space at Abbey Road studios. (May 2023) - Jubb, Darren
This research considers the relationship between accounting and physical space, focusing on the creation of musical recordings within the musical and 'magical' space of Abbey Road Studios during the 1960s. Building on prior studies that have utilised the work of Foucault to theorise accounting's ability to contribute to making space more disciplinary, this study highlights how, at the beginning of the 1960s, accounting was part of a wider regime that rendered the non-disciplinary, musical space of the recording studio visible and controllable in order to standardise musical recording practices. As the period progressed, and against a backdrop of cultural revolution in 1960s Britain, existing rules and procedures were circumvented by musicians, producers and engineers who utilised experimental practices to create non-standardised, 'magical', sonic worlds. Control over the musical space of the recording studio waned and so too did accounting's ability to capture and manage the emergent creative practices.